Protoenzymes: The Case of Hyperbranched Polymer-Scaffolded ZnS Nanocrystals - Irena Mamajanov; Melina Caudan; Tony Z. Jia (Life, 2020)
Enzymes are biological catalysts that are comprised of small-molecule, metal, or cluster catalysts augmented by biopolymeric scaffolds. It is conceivable that early in chemical evolution, ancestral enzymes opted for simpler, easier to assemble scaffolds. Herein, we describe such possible protoenzymes: hyperbranched polymer-scaffolded metal-sulfide nanocrystals. Hyperbranched polyethyleneimine (HyPEI) and glycerol citrate polymer-supported ZnS nanocrystals (NCs) are formed in a simple process. Transmission electron microscopy (TEM) analyses of HyPEI-supported NCs reveal spherical particles with an average size of 10 nm that undergo only a modest aggregation over a 14-day incubation. The polymer-supported ZnS NCs are shown to possess a high photocatalytic activity in an eosin B photodegradation assay, making them an attractive model for the study of the origin of life under the “Zn world” theory dominated by a photocatalytic proto-metabolic redox reaction network. The catalyst, however, could be easily adapted to apply broadly to different protoenzymatic systems.